2003
DOI: 10.1038/sj.npp.1300210
|View full text |Cite
|
Sign up to set email alerts
|

Central Muscarinic Acetylcholine Receptor Availability in Patients Treated with Clozapine

Abstract: Clozapine is the prototypical atypical antipsychotic. In vitro, clozapine antagonizes a broad range of receptors, including dopamine, serotonin and muscarinic acetylcholine receptors. In vivo, receptor occupancy studies have shown moderate dopamine D 2 receptor blockade as well as high serotonin 5HT 2 receptor blockade for clozapine. Using [I-123]IQNB SPECT, we explored the influence of clozapine on muscarinic receptors in vivo. Eight schizophrenia patients underwent a total of 12 [I-123]IQNB SPECT scans after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…After treatment with a daily dose of at least 200 mg of clozapine (mean 275.0 mg/day), the muscarinic receptor occupancy was 45% for the basal ganglia and 58% for the cortex. 100 In direct comparison of these data, clozapine results in a significantly lower availability of the muscarinic receptor than olanzapine. 101 These results of decreased muscarinic receptor availability in vivo after treatment with clozapine and olanzapine are consistent with in vitro studies, in which both antipsychotic drugs showed high affinity to all subtypes of the muscarinic receptor.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…After treatment with a daily dose of at least 200 mg of clozapine (mean 275.0 mg/day), the muscarinic receptor occupancy was 45% for the basal ganglia and 58% for the cortex. 100 In direct comparison of these data, clozapine results in a significantly lower availability of the muscarinic receptor than olanzapine. 101 These results of decreased muscarinic receptor availability in vivo after treatment with clozapine and olanzapine are consistent with in vitro studies, in which both antipsychotic drugs showed high affinity to all subtypes of the muscarinic receptor.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…The number of M 1 /M 4 muscarinic acetylcholine receptors (mAChRs) have also been found to be reduced relative to normal postmortem brains in several areas including the hippocampus (Crook et al, 2000), prefrontal cortex (Crook et al, 2001) and striatum (Dean et al, 1996). Likewise, single photon emission computed tomography (SPECT) in living, unmedicated schizophrenic patients revealed fewer mAChRs in frontal, temporal, and occipital cortex as well as in the striatum and thalamus compared to control subjects (Raedler et al, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…As well, it is known that clozapine is a potent antimuscarinic agent (Miller and Hiley 1974) with high affinity for all five human muscarinic receptors (Bolden et al 1992) where it may function as either a partial agonist (Zorn et al 1994;Olianas et al 1999;Sur et al 2003) or an antagonist (Bolden et al 1992;Olianas et al 1999), depending upon the muscarinic receptor subtype, cellular milieu and levels of receptor expression. It is not surprising, therefore, that clozapine treatment is associated with a high degree of occupancy of central muscarinic receptors in vivo (Raedler et al 2003a). These findings have led to the proposition, first suggested by Pfeiffer and Jenney (1957), that stimulation of central muscarinic receptors might prove salutary for, perhaps, the positive and negative symptoms of schizophrenia (Bymaster et al 1998(Bymaster et al , 2002Tandon 1999).…”
Section: Introductionmentioning
confidence: 99%